Heparin, Heparan Sulphate and Sepsis: Potential New Options for Treatment - John Hogwood; Elaine Gray; Barbara Mulloy (MDPI AG, 2023)
Sepsis is a life-threatening hyperreaction to infection in which excessive inflammatory and immune responses cause damage to host tissues and organs. The glycosaminoglycan heparan sulphate (HS) is a major component of the cell surface glycocalyx. Cell surface HS modulates several of the mechanisms involved in sepsis such as pathogen interactions with the host cell and neutrophil recruitment and is a target for the pro-inflammatory enzyme heparanase. Heparin, a close structural relative of HS, is used in medicine as a powerful anticoagulant and antithrombotic. Many studies have shown that heparin can influence the course of sepsis-related processes as a result of its structural similarity to HS, including its strong negative charge. The anticoagulant activity of heparin, however, limits its potential in treatment of inflammatory conditions by introducing the risk of bleeding and other adverse side-effects. As the anticoagulant potency of heparin is largely determined by a single well-defined structural feature, it has been possible to develop heparin derivatives and mimetic compounds with reduced anticoagulant activity. Such heparin mimetics may have potential for use as therapeutic agents in the context of sepsis.